INFLUENCE OF PREDECESSORS ON YIELD AND GRAIN QUALITY OF NEW WINTER DURUM WHEAT VARIETIES - Shakaliy, S. M.; Bagan, A. V.; Yurchenko, S. O.; Сhetveryk, О. О. (Scientific Progress & Innovations, 2021)
Increasing yield potential has always been and remains fundamentally important in breeding programs. But modern varieties must be not only high-yielding, producing high quality products, but also resistant to unfavorable environmental factors, highly adapted, highly homeostatic. Only high variety adaptability (stip-ulated homeostatic nature of its genotype) can ensure the yield stability in different environmental conditions. The results of studying the influence of predecessors on the yield and grain quality of new winter durum wheat varieties are presented in the article. The research was conducted during 2018–2020 with Pryazovska and Shulyndinka winter durum wheat varieties in Poltava region to study the impact of predecessors on yield and grain quality, and the results showed that, according to the average data (2018–2020), the level of grain yield depended on weather conditions by 35 %, on the variety – by 25 %, and on the predecessor – by 20 %. Pryazovska variety after soybean predecessor had a yield of 5.62 t/ha, which was 0.04 t/ha higher than after winter rape predecessor. Shulyndinka variety was characterized by higher yields after winter rape predecessor (5.90 t/ha) than after soybean (5.81 t/ha). Hardness index is important for winter durum wheat, as it characterizes the internal grain structure. Hardness is required for further processing of winter durum wheat grain into pasta products. 2019 was characterized by the highest hardness. Shulyndinka variety had hardness index of 87% after soybean forecrop and up to 86 % after winter rape. For three years (2018–2020), the highest protein weight fraction in winter durum wheat grain (15.0–14.8 %) was formed, on the average, in Pryazovska variety after two predecessors. Shulyndinka varie-ty had a slightly lower protein weight fraction (14.4–14.6 %). Thus, according to the conducted research, the best precursor for Pryazovska variety was soybean, and for Shulyndivka – winter rape.